Relationship Between Premature Rupture Of Membranes And The Incidence Of Asphyxia In Newborns At RSUD Dr. Soegiri Lamongan - Lilin Turlina; Ratih Indah Kartikasari; Elia Ika Rahmawati (Universitas Islam Lamongan, 2021)
Neonatal mortality rate is one indicator to assess health in the community. According to WHO, the main causes of neonatal death include prematurity, neonatal asphyxia, and neonatal sepsis. The purpose of this study was to analyze the relationship between premature rupture of membranes and asphyxia in newborns at RSUD Dr. Soegiri Lamongan. This study used an analytical method with a cross sectional approach. The total sample was 240 newborns, consisting of babies with asphyxia and normal babies. Sampling with simple random sampling. Collecting data using a check list. Data taken from patient medical records (secondary data). Data analysis used the Chi Square test with a significance level of α <0.05. The results of the analysis with the Chi square test showed that the value of Asympt.Sig. (2-sided) on the Pearson Chi square test is 0.000 less than 0.05. So it can be concluded that there is a significant relationship between PROM/KPD and the incidence of neonatal asphyxia in the delivery room of dr. Soegiri Lamongan. Asphyschia neonatorum is a complication of newborns which one of the contributing factors is PROM. Therefore, emergency obstetric and newborn care efforts should be strengthened to prevent neonatal asphyxia. It is hoped that health workers in the delivery room will carry out careful monitoring of labor, and identify and take appropriate measures to help reduce the occurrence of neonatal asphyxia